Postural Dysfunction in Children With Cerebral Palsy: Some Implications for Therapeutic Guidance - Carlberg, Eva Brogren (Hindawi Publishing Corporation, 2005)
Postural problems play a central role in the motor dysfunction of children with cerebral palsy (CP). Therefore, they spend more time in sitting than in standing to perform vital tasks of daily life. The focus of this article is to describe the pathophysiology of postural control in sitting and outline some implications for management and treatment. In general, children with CP exhibit muscular activity counteracting forces that disturb equilibrium. Only ‘non-sitting’ children with severe CP lack such ‘direction-specific’ adjustments, possibly ruling out achievement of independent sitting. Most frequently, the children display dysfunctions in the adaptation of the adjustment. Typical characteristics of this adaptation in children with CP are a top-down recruitment of pos tural muscles, an excessive degree of antagonistic coactivation, and an incomplete adaptation of the EMG-amplitude to task specific constraints. Despite our knowledge on the pathophysiology underlying the postural problems in children with CP, little ’high-level’ evidence (according to Sackett) exists on how different interventions can affect these problems. Therapeutic attention to promote motor performance in sitting focuses on adaptive seating, tilting of the support surface, and ample, variable training in motivating settings. The challenge facing us now is to provide evidence about the efficacy of specific treatment approaches facilitating that children reach an optimal level of functioning in daily life.